The prevailing paradigm as a hindrance to conservation - Michael L. Morrison; Bret A. Collier; Heather A. Mathewson; Julie E. Groce; R. Neal Wilkins (Wildlife Society Bulletin)
Abstract We review the history of population and ecological knowledge of the golden‐cheeked warbler (Setophaga chrysoparia). We highlight how incomplete information on distribution and abundance has led to substantial misunderstanding on species status and associated conservation goals. We discuss how once a paradigm is established, subsequent studies unconsciously fortify accepted understanding regardless of the paradigm's accuracy. For the golden‐cheeked warbler, understanding of the species at the time of listing in 1990 was based on either incorrect or untested assumptions of species distribution within available habitats. Adhering to untested assumptions led to development of priorities for research and management that were well‐intentioned but largely misguided. Ample information on the distribution of the warbler's habitats existed, however, which should have encouraged questions into the basis of population conditions when developing management prescriptions. Current knowledge clearly indicates that a new paradigm for the warbler is needed, that being one of a widely distributed species that is preadapted to occur within a variety of environmental conditions. © 2012 The Wildlife Society.